Abductive Research Strategy(ARS) & The Generation Of Grounded Concepts - Two Empirical Examples - Ong, Beng Kok (2010)
Abductive Research Strategy (ARS) is one distinctive type of qualitative research developed by Blaikie (1993, 2000, 2007, 2010), which refers to the process of constructing theories or typologies that are grounded in everyday activities and in the language and meanings of social actors.